The Correlation of Some Soil Chemical Properties with Phosphorus Uptake of Lowland Rice on Kaolinitic and Smectitic Soils - M. MASJKUR; ANTONIUS KASNO (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2008)
Determining relationship between soil properties and phosphorus uptake is important to support P fertilizer recommendation. The objective of this research was to determine the relationship between some soil chemical properties and phosphorus uptake of lowland rice on kaolinitic and smectitic soils. Field experiments were conducted in Lampung kaoliniticpaddy soils and East Java smectitic paddy soils with low, medium, and high P content variabilities. The experiments used completely randomized block design with four replications. The treatments consist of five P fertilizer levels that were 0, 23, 46, 69, dan 115 kg P2O5 ha-1, applied as superphosphate (SP-36). In kaolinitic soils, P uptake response with P fertilizer was not significant, whereas in smectitic soils P uptake response was significant. In kaolinitic soils, organic C correlated positively withP uptake of lowland rice, while the correlation of pH, clay content, exchangeable Ca, Fe, and Al were not significant. In smectitic soils, organic C correlated negatively with P uptake of lowland rice, while the correlation of pH, clay content, exchangeable Ca, Fe, and Al were not significant. Thus, increasing organic matter in kaolinic soils will increase P uptake of lowland rice, while in smectitic soils increasing organic matter will decrease P uptake.